The Characteristic Properties of Magnetostriction and Magneto-Volume Effects of Ni2MnGa-Type Ferromagnetic Heusler Alloys - Takuo Sakon (Materials, 2019)
In this article, we review the magnetostriction and magneto-volume effects of Ni2MnGa-type ferromagnetic Heusler alloys at the martensitic, premartensitic, and austenitic phases. The correlations of forced magnetostriction (ΔV/V) and magnetization (M), using the self-consistent renormalization (SCR) spin fluctuation theory of an itinerant electron ferromagnet proposed by Takahashi, are evaluated for the ferromagnetic Heusler alloys. The magneto-volume effect occurs due to the interaction between the magnetism and volume change of the magnetic crystals. The magnetic field-induced strain (referred to as forced magnetostriction) and the magnetization are measured, and the correlation of magnetostriction and magnetization is evaluated. The forced volume magnetostriction ΔV/V at the Curie temperature, TC is proportional to M4, and the plots cross the origin point; that is, (M4, ΔV/V) = (0, 0). This consequence is in good agreement with the spin fluctuation theory of Takahashi. An experimental study is carried out and the results of the measurement agree with the theory. The value of forced magnetostriction is proportional to the valence electron concentration per atom (e/a). Therefore, the forced magnetostriction reflects the electronic states of the ferromagnetic alloys. The magnetostriction near the premartensitic transition temperature (TP) induces lattice softening; however, lattice softening is negligible at TC. The forced magnetostriction at TC occurs due to spin fluctuations of the itinerant electrons. In the martensitic and premartensitic phases, softening of the lattice occurs due to the shallow hollow (potential barrier) of the total energy difference between the L21 cubic and modulated 10M or 14M structures. As a result, magnetostriction is increased by the magnetic field.